The presence of absence in art - Godínez , Mónica Elisa Contreras (Farol, 2024)
This text presents a reflection on artistic production that raises the relevance in contemporary art of mnemonic processes translated into works that express complex relationships with the disappearance and persistence of images, in this case the work that we will review was mostly made in the pandemic period which modified its resources that were determined by the intimate and domestic space.